FINAL STUDENT CAREER SELECTION FROM : HOLLAND THEORY PERSPECTIVE - Sartika, Dewi; Daulay, Annisa Arrumaisyah (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
One of the most important decision-making processes of a person is choosing a career. What happens in his life will be influenced by the choices he will make. Because it is one of the decision-making processes that individuals go through after going through how many stages of development in their lives. Career selection is also an aspect of a person's personality or social life that cannot be avoided. Certain career choices are very important and tailoring a person's career reflects their personality. Research on descriptive qualitative is this type of research. Using interviews on final year students. Being the source of data for this study regarding the difficulties of final year students choosing careers based on the findings of interview analysis and final year student researchers facing difficulties in choosing their career path. So that students in the final year cannot choose a career path, what will be done to find out the problems faced and to design solutions. In reducing the problems that occur, namely career guidance planning in increasing the exploration of final students.